Study of morbidity pattern of under 5-year children in Jaipur - Vinay Sharma; Nisha Kumari Ojha (Wolters Kluwer Medknow Publications, 2021)
Objectives: Early childhood under 5 years of age is a period of life with a high level of morbidity. Respiratory, gastrointestinal, and other infections are the most common morbidities in this age group. The present study aims to find out the morbidity pattern of under-5-year children in Jaipur and estimate the association between and also determine the factors affecting these conditions. Methods: A cross-sectional study was conducted on 1007 under 5-year children based on a duly prepared survey pro forma. Mothers and head of family of children between under5 years of age were enquired about the morbidity in the past 3 months. Results: In the present study, cough (34.4%), fever (27.7%), nutrition anemia (24.8%), malnutrition (22.8%), flu (19.5%), hard stool (18.8%), and diarrhea (11.1%) were common morbidities observed among under-five children. The following variables were significantly associated (P < 0.05) with the variable "morbidity:" age (year), height (cm), head circumference (cm), vaccination scar, duration of breastfeeding, birth order, and poor general hygiene. Conclusion: There was an association between morbidity and age, height, head circumference, vaccination duration of breastfeeding, and poor hygiene and no relationship found between socioeconomic status and other factors such as amenities, education of parents, and family size.